2017
DOI: 10.3389/fphar.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sirtuin 3 by Silybin Attenuates Mitochondrial Dysfunction in Cisplatin-induced Acute Kidney Injury

Abstract: Silybin is a secondary metabolite isolated from the seeds of blessed milk thistle (Silybum marianum) that has anti-inflammatory, antioxidative, antifibrotic, and antitumor properties. Here, we showed that silybin protected against cisplatin-induced acute kidney injury (AKI) by improving mitochondrial function through the regulation of sirtuin 3 (SIRT3) expression. Male SV129 and SIRT3 knockout (KO) mice were administered a single intraperitoneal (i.p.) injection of cisplatin with or without treatment with sily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…In the present study, we demonstrated that silibinin protected osteoblasts from AGE-induced apoptosis. Evidence has also suggested that silibinin exerts beneficial effects against mitochondrial damage under pathological conditions 24 , 25 . Our results revealed that the protective effects of silibinin against AGEs-induced apoptosis of osteoblastic cells were achieved via the attenuation of mitochondrial OS and dysfunction, restoration of mitochondrial morphology and aberrant mitochondrial fission/fusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that silibinin protected osteoblasts from AGE-induced apoptosis. Evidence has also suggested that silibinin exerts beneficial effects against mitochondrial damage under pathological conditions 24 , 25 . Our results revealed that the protective effects of silibinin against AGEs-induced apoptosis of osteoblastic cells were achieved via the attenuation of mitochondrial OS and dysfunction, restoration of mitochondrial morphology and aberrant mitochondrial fission/fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Pine bark extract with potent anti-oxidant activity attenuates cisplatin-induced kidney injury of rats (Lee et al, 2017 ). Silybin (a main flavonoid of S. marianum ) as a pharmacological activator of SIRT3, has capable of protection against cisplatin-induced tubular cell apoptosis and acute kidney injury by improving mitochondrial function (Li et al, 2017 ). Origanum majorana is commonly known as marjoram in traditional medicine, which possesses anti-oxidant, anti-microbial and anti-inflammatory activities (Leyva-Lopez et al, 2017 ).…”
Section: Capacity To Relief Nephrotoxicitymentioning
confidence: 99%
“…Silibinin, the most famous and active compound isolated from Silybum marianum (milk thistle) traditionally used to protect from liver injury, could induce apoptosis related to mitochondrial Ca 2+ influx in C. albicans cells [ 84 , 85 ]. Silibinin could alleviate mitochondrial dysfunction in mice model of cisplatin-induced acute kidney injury through Sirt3 activation, although in vitro proapoptotic effects through inducing ROS production have been also reported [ 86 , 87 ]. The safe profile with silibinin, evidenced by marketed health food and clinical trials, makes silibinin a very promising candidate for antifungal therapies against Candida infections although there is still a long way to go [ 88 ].…”
Section: Compounds Targeting Mitochondriamentioning
confidence: 99%